Mapping vulnerability for increased COVID-19 susceptibility and worse outcomes: a scoping review - Couto, Rodrigo de Macedo; dos Santos, Daniel Gonçalves; Sanine, Patrícia Rodrigues; Pires dos Santos, Andrea; Kmetiuk, Louise Bach; Biondo, Alexander Welker; Boing, Alexandra Crispim (Frontiers in Public Health, 2024)
Introduction Infectious diseases can spread rapidly in the globalized world, and the complex intersection of individual, social, economic, and cultural factors make it difficult to identify vulnerabilities in the face of pandemics. Methods Therefore, this study aimed to identify vulnerability factors to infection and worse outcomes associated with COVID-19. This is a scoping review study of six databases that selected publications between 2019 and 2023, focusing on individual, social, and programmatic dimensions of vulnerability. The results were recorded in a spreadsheet and analyzed, considering the interrelationships among these dimensions. Results A total of 45 articles were included in the review. Content analysis was conducted using the theoretical framework of health vulnerability, which divides vulnerability into individual, social, and programmatic dimensions. Race/ethnicity, homelessness, incarceration, socioeconomic level, food insecurity, and remote areas were classified as social dimensions. On the other hand, cancer, cardiovascular disease, HIV/AIDS, alcoholism, advanced age, obesity, mental disorders, diabetes, kidney disease, and pregnancy were classified as individual dimensions. None of the publications found explicitly mentioned programmatic vulnerabilities. Discussion The research found that social vulnerabilities reinforce individual vulnerabilities, creating a vicious cycle. In addition, programmatic vulnerabilities reinforce this relationship. This study emphasizes that public policies should address these different dimensions of vulnerability. It suggests that this information should be incorporated into health surveillance and future decision-making to face new pandemics. Systematic review registration https://archive.org/details/osf-registrations-wgfmj-v1.